L’altérité et le tourisme : construction du soi et d’une identité sociale - Anne-Marie d’Hauteserre (Espace populations sociétés, 2009)
This article examines one of the reasons why third world alterity is one of the motors of tourism. What do travelers seek when they visit those remote sites? A stop in a village built by the government of Myanmar where women with exotic cultural practices can be photographed led me to raise this question. Landscapes as much as spaces, including tourist destinations, are socially constructed to enable those who cross them to confirm their subjectivity. Looking at attitudes and practices of tourists and tour operators allows us to explore how exotic or everyday landscapes support selective self-identities and a hierarchy of social differentiations. Tourists do not look for true alterity but rather for the possibility of encountering its romantic mystery whose staging makes more familiar. The form of exoticism marketed by tourism is but a pale imitation of voyages of exploration of past centuries. However, it permits tourists who enjoy only short holidays, to construct some cultural capital while they work on maintaining their social hierarchical position relative to local residents and other visitors. Far from leading to an understanding of others, the staging of their alterity is used for self-identity construction and to justify such practices. These practices do remain constrained, however, by the social and cultural habitus of tourists, whatever their origins, and by the demands of international capital.